2008
DOI: 10.2215/cjn.01730408
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rituximab on Morphofunctional Abnormalities of Membranous Glomerulopathy

Abstract: In human IMN, treatment-induced NS remission is associated with restoration of sodium homeostasis and kidney hemodynamics, and regression of the glomerular changes underlying proteinuria. These effects are likely to translate into long-term renoprotection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 35 publications
(28 reference statements)
4
33
0
2
Order By: Relevance
“…To note, the finding that in patients achieving complete or partial remission serum albumin increase to normal range was associated with significant reduction of albumin fractional clearance, allowed us to conclude that amelioration of the signs of the nephrotic syndrome was likely explained by improved glomerular sieving function in this population. Combined to previous evidence that remission of proteinuria is also associated with regression of kidney structural and ultra-structural changes, 40 these findings can be taken to suggest that rituximab therapy might have protective effects against renal disease progression also in the long term. 41 By and large, the above findings support the notion that rituximab therapy is at least as effective and remarkably safer than immunosuppressive regimens including steroids and alkylating agents.…”
Section: Discussionsupporting
confidence: 52%
“…To note, the finding that in patients achieving complete or partial remission serum albumin increase to normal range was associated with significant reduction of albumin fractional clearance, allowed us to conclude that amelioration of the signs of the nephrotic syndrome was likely explained by improved glomerular sieving function in this population. Combined to previous evidence that remission of proteinuria is also associated with regression of kidney structural and ultra-structural changes, 40 these findings can be taken to suggest that rituximab therapy might have protective effects against renal disease progression also in the long term. 41 By and large, the above findings support the notion that rituximab therapy is at least as effective and remarkably safer than immunosuppressive regimens including steroids and alkylating agents.…”
Section: Discussionsupporting
confidence: 52%
“…Kidney repair has been definitely documented in seven proteinuric patients with idiopathic membranous nephropathy treated with the anti-CD20 mAb, rituximab; these patients, in parallel with complete remission of the nephrotic syndrome, showed reabsorption of characteristic subepithelial electron-dense immune deposits and reversion of foot process effacement and loss of intact slit diaphragms at repeat biopsy evaluation. 89 Consistently, the possibility of morphologic regression of chronic structural changes was confirmed by a morphofunctional study showing that in eight patients with type 1 diabetes and mild to advanced nephropathy, renal histology lesions regressed after 10 years of euglycemia made possible by pancreas transplantation. 90 ACE inhibitors can boost renal repair by promoting survival and repair of podocytes, preventing mesangial cell hyperplasia, and inducing glomerular endothelial cell remodeling.…”
Section: From Nephroprotection To Kidney Regeneration: Can the Kidneymentioning
confidence: 76%
“…The most recent study from Ruggenenti et al found that the glomerular changes of MN, detected on initial biopsy, regressed alongside clinical improvement in seven patients who achieved complete remission on rituximab therapy and consented for repeat biopsy (30). There were no controls in this study (such as subjects with refractory disease or subjects who achieved spontaneous remission without therapy), but the authors speculate that rituximab may have led to this morphologic improvement by removing the kidney's exposure to pathogenic antibodies, akin to a well known experiment in which kidneys from rats with Heymann nephritis, when transplanted into nondiseased animals, saw resolution of subepithelial deposits with remission of proteinuria (49).…”
Section: Discussionmentioning
confidence: 99%
“…The remaining were uncontrolled case series (of which five emanate from a single center) with a total of 65 patients-specifically, 50 patients reported in the most recent series by Remuzzi's group (30), and 15 patients reported by Fervenza et al (25). Looking only at the case series, 10 of 50 patients (20%) followed by Remuzzi and colleagues over 6 yr and 2 of 15 patients (13%) reported by Fervenza et al achieved complete remission.…”
Section: Rituximab Treatment Outcomesmentioning
confidence: 99%